2007
DOI: 10.1007/s10571-007-9161-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Types in the Human Anterior Ventral Thalamic Nucleus: A Golgi Study

Abstract: Neurons in the anterior ventral (AV) thalamic nucleus of human adults were impregnated by Golgi-Kopsch impregnation method. Results showed that at least three morphological types of neurons could be recognized in the human AV thalamic nucleus. Type I neurons were medium to large with rich dendritic arborization. Both tufted and radiating dendritic branching patterns were seen in almost every neuron of this type. Only the initial axonal segments of these cells were impregnated suggesting that these axons were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Golgi-type I nerve cells found in this study were found to be generally similar to their counterparts previously described in other thalamic nuclei including the human anterior ventral, ventral anterior, ventral posterior, ventral lateral nuclei as well as medial geniculate, and lateral geniculate bodies (Al-Hussain Bani Hani et al, 2008;Braak & Braak, 1984;Grodd et al, 2020;Hajdu, Hassler, & Somogyi, 1982;Hani et al, 2007;Hazlett et al, 1976;Pearson & Haines, 1980;Schaltenbrand & Wahen, 1977;Tseng & Royce, 1986). In all these studies, Golgi-type I nerve cells were found to have medium to large cell bodies and dense dendritic trees.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Golgi-type I nerve cells found in this study were found to be generally similar to their counterparts previously described in other thalamic nuclei including the human anterior ventral, ventral anterior, ventral posterior, ventral lateral nuclei as well as medial geniculate, and lateral geniculate bodies (Al-Hussain Bani Hani et al, 2008;Braak & Braak, 1984;Grodd et al, 2020;Hajdu, Hassler, & Somogyi, 1982;Hani et al, 2007;Hazlett et al, 1976;Pearson & Haines, 1980;Schaltenbrand & Wahen, 1977;Tseng & Royce, 1986). In all these studies, Golgi-type I nerve cells were found to have medium to large cell bodies and dense dendritic trees.…”
Section: Discussionsupporting
confidence: 87%
“…In the human AV, two morphologically different types of neurons were found, one corresponded to Golgi-type I with large body and dense dendritic trees while the other type corresponded to Golgi-type II with small body, few branches and grape-like dendritic appendages. Although long segments of the axons of these small neurons were impregnated in one study (Hani et al, 2007), no local axonal branches were found. This may indicate that these neurons could be in fact thalamocortical projecting neurons rather than interneurons which come in agreement with the result of the other study (Somogyi et al, 1973).…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations